(untitled) (Vietnam Journal of Community Medicine, 2026)
Intraosseous lipoma is one of the rarest primary bone tumors in the body. The reported incidence rate is <0.1% of all primary bone tumors. The majority of intraosseous lipoma cases in the calcaneus are asymptomatic and are often discovered incidentally when the patient undergoes X-rays or are misdiagnosed in the clinical context of heel pain, such as plantar fasciitis, retrocalcaneal bursitis, stress fracture, simple bone cyst, aneurysmal bone cyst, osteoblastoma, non-ossifying fibroma, giant cell tumor, chondroblastoma, fibrous dysplasia, and chondrosarcoma. This is a case of a 37-year-old male patient who presented with persistent heel pain for about 3 months, with no history of trauma, and was diagnosed and treated for plantar fasciitis without improvement. X-ray images showed an osteolytic lesion within the calcaneus, and Magnetic Resonance Imaging (MRI) revealed a well-circumscribed mass with signal characteristics of adipose tissue. The patient underwent surgical curettage of the tumor and allograft bone grafting. At 1-year follow-up, the patient was pain-free, with good functional outcomes and good graft consolidation observed on X-ray films.